MODERN CLINICAL AND LABORATORY METHODS FOR ASSESSING THE COURSE OF PRIMARY TUBERCULOSIS IN CHILDREN AND ADOLESCENTS - Umarova T. A.; Kudratova Z. E.; Nafasova Zarina (Web of Journals Publishing, 2024)
Children and adolescents are an age group that requires special attention during the period of increasing tuberculosis morbidity. Significant deterioration of the epidemiologic situation, clinical polymorphism of tuberculosis in children, manifested both by asymptomatic and pronounced picture with extensive destructive changes, low frequency of bacterial excretion requires improvement of methods for diagnosing tuberculosis in children [8, 9,10,11,12,13].
Keywords: Laboratory diagnostics of tuberculosis, internal environment, dynamic changes, toxic granularity of neutrophils.